Postoperative Nomogram for Disease Recurrence and Cancer-Specific Death for Upper Tract Urothelial Carcinoma: Comparison to American Joint Committee on Cancer Staging Classification - Ehdaie, Behfar; Shariat, Shahrokh F; Savage, Caroline; Coleman, Jonathan; Dalbagni, Guido (Urology Journal, 2014)
<!–[if gte mso 9]> Normal.dotm 0 0 1 269 1534 Urologic Oncology 12 3 1883 12.0 <![endif]–><!–[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> <!–StartFragment–> Abstract Purpose: We sought to develop prognostic models to predict disease recurrence and cancerspecific mortality in patients with upper tract urothelial carcinoma (UTUC) who underwent radical nephroureterectomy (RNU). Materials and Methods: Data on 253 patients treated with RNU between 1995 and 2008 at a single high-volume tertiary referral center were analyzed. Statistically and clinically significant patient and tumor characteristics were identified in a univariate analysis and incorporated into a multivariable Cox regression model. The model was compared to the 2010 American Joint Committee on Cancer (AJCC) staging classification using the concordance index (c-index), corrected for statistical optimism using bootstrap methods. Results: Five-year recurrence-free survival (RFS) and cancer-specific survival (CSS) rates were 73% [95% confidence interval (CI): 66-79%)] and 78% (95% CI: 71-84%), respectively. On multivariate analysis, higher preoperative glomerular filtration rate (GFR) was associated with better CSS [hazard ratio (HR) per 1 mL/min/m2 increase in GFR for CSS: 0.74; P = .002)], while higher pathologic stage (HR for pT2: 2.99 and for ≥ pT3: 7.34; P < .001) and lymph node involvement (HR: 3.75; P < .001) were associated with worse CSS; results were similar for RFS. The ability of the final models, which included preoperative GFR, lymph node status, pathologic grade, and stage, to predict RFS and CSS (c-index 0.82 and 0.83, respectively) was similar to that of the 2010 AJCC staging classification (c-index 0.80 and 0.81, respectively). Conclusion: Given the data-dependent selection of variables in this single institution cohort, it is unlikely that the marginal improvement found with these prediction models would importantly impact clinical decision-making or improve patient care. The 2010 AJCC staging classification alone is very accurate and should continue to guide follow-up after RNU. <!–EndFragment–>